Comparative Effect of Computer Tutorial and Computer Drill and Practice Technique on Secondary School Students’ Achievement in Computer Studies - OSUAFOR, Abigail M; ONOH, Theresa N (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The study investigates the comparative effect of computer tutorial and computer drill and practice techniques on secondary school students’ achievement in computer studies. Five research questions and four hypotheses guided the study. Quasi-experimental research design, specifically the pretest posttest which involved group of students assigned to treatment groups was adopted for the study. The study was carried out in Awka Education Zone of Anambra State. The population for the study was 2,250 SS II students from 15 government-owned co-educational secondary schools in Awka Education zone of Anambra State. The sample size for the study was 78 SSII students selected through balloting sampling. A 25 item multiple choice question of CSAT was the instrument used to collect data. One experimental group was taught using computer tutorial technique while the other experimental group was taught using computer drill and practice technique. Mean and standard deviation were used to answer the research questions and ANCOVA was used to test the null hypotheses at 0.05 level of significance. The findings revealed that students taught using computer drill and practice technique achieved more than those taught with computer tutorial technique. Based on the findings, it was recommended among others that the use of computer drill and practice technique should be embraced by teachers to convey their instruction in classroom since it has been found to be effective in computer studies students’ achievement.